2001
DOI: 10.1163/156856201753113088
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bone cements prepared with functionalized methacrylates and hydroxyapatite

Abstract: Bone cements prepared with methyl methacrylate and either methacrylic acid or diethyl amino ethyl methacrylate as comonomers were characterized by infrared spectroscopy, nuclear magnetic resonance, gel permeation chromatography, dynamic mechanical thermal analysis, and mechanical testing. Selected formulations containing these functionalized methacrylates were filled with hydroxyapatite and studied in terms of their properties in tension, compression and bending, and X-ray diffraction. It was found that residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 18 publications
2
25
0
5
Order By: Relevance
“…However, when the amount of filler is increased to 30% by weight, the tensile modulus increases from 2.2 to 2.8 GPA ( p < 0.05) and ultimate strain ( p < 0.05) is reduced. Islas‐Blancas et al found a decrease in tensile modulus when HA powder was used as a filler, and explained this decrease as a result of poor mixing and poor adhesion between matrix and filler 19. Canul‐Chuil et al also reported that the presence of HA powder in an acrylic bone cement decreased the tensile modulus 18.…”
Section: Results and Discusionmentioning
confidence: 99%
“…However, when the amount of filler is increased to 30% by weight, the tensile modulus increases from 2.2 to 2.8 GPA ( p < 0.05) and ultimate strain ( p < 0.05) is reduced. Islas‐Blancas et al found a decrease in tensile modulus when HA powder was used as a filler, and explained this decrease as a result of poor mixing and poor adhesion between matrix and filler 19. Canul‐Chuil et al also reported that the presence of HA powder in an acrylic bone cement decreased the tensile modulus 18.…”
Section: Results and Discusionmentioning
confidence: 99%
“…4(b)). Generally, the presence of hydroxyapatite clusters within the polymeric matrix suggests not only poor mixing but also poor adhesion between matrix and fillers [38]. Considering that the hydroxyapatite particles have been treated with a silane coupling agent and, therefore, the adhesion between HA and PMMA was improved as demonstrated by the results in compressive tests, then it is possible to postulate that the surface treatment is mainly improving the interfacial adhesion to the dispersion of particles.…”
Section: Bending Propertiesmentioning
confidence: 99%
“…For example, the polymer matrix may be nonresorbable and non-injectable (e.g., thermoplastics such as PAEK, [40][41][42][43] UHMWPE, 44 and HDPE 1-6 ), nonresorbable and injectable (e.g., acrylics such as PMMA [45][46][47][48][49][50][51][52] and bis-GMA/TEG-DMA 52-57 ), bioresorbable and non-injectable (e.g., collagen [58][59][60][61] or poly--hydroxy esters such as PLLA and PLGA 62-68 ), or bioresorbable and injectable (e.g., collagen, calcium phosphate cements [68][69][70][71] and various hydrogels [72][73][74][75]. (Collagen may function as either noninjectable or injectable depending on whether it has been cross-linked prior to implantation.…”
Section: The Polymer Matrixmentioning
confidence: 99%